Numerical and experimental investigation of optimized triangular microchannels using MXene-based nanofluids for enhanced microfluidic thermal performance - Abdullah Aziz; Abdulrahman Agha; Shoaib Anwer; Eiyad Abu‑Nada; Anas Alazzam (International Journal of Thermofluids)
This study presents a comprehensive numerical and experimental investigation to optimize the thermal performance of microfluidic devices using MXene-based nanofluids. Four distinct serpentine microchannel geometries—triangular, square, sinusoidal, and sawtooth—were evaluated for their heat transfer performance. Numerical results identified the triangular microchannel as the optimal design, offering significant heat transfer enhancement. Using water-based MXene nanofluids, thermal performance was assessed at varying concentrations (0.005–0.02 wt.%) and Reynolds numbers (0.5–4.5). The numerical models demonstrated excellent agreement with experimental data, achieving up to 98.5 % accuracy for heat fluxes ranging from 100 to 500 mW/cm². The results revealed that MXene nanofluid concentrations of 0.005 wt.% and 0.01 wt.% increased the Nusselt number by 85.52 % and 89.06 %, respectively, compared to pure water. These findings highlight that the combination of an optimized triangular microchannel geometry and well-calibrated MXene nanofluid concentrations significantly enhances heat transfer performance in microfluidic devices. This study underscores the potential of MXene-based nanofluids to advance thermal management systems for microfluidic applications.